5 Commandments [technology laws and rules of thumb]. - Ross, P.E.
There are sublime, silly, real and true laws, and folksy rules of thumb laws that have come up from mathematical observations, pithy pronouncements, and even a few enduring self-fulfilling prophecies about technology. The article discusses how some laws have fared in time. These laws include: Moore's Law - the number of transistors on a chip doubles annually; Rock's Law - the cost of semiconductor tools doubles every four years; Machrone's Law the PC you want to buy will always be 5000 dollars; Metcalfe's Law - a network's value grows proportionately to the number of its users squared; and Wirth's Law - software is slowing faster than hardware is accelerating.
Keywords: Machrone's Law; Metcalfe's Law; Moore's Law; Rock's Law; Wirth's Law; Network value; Number of users; Personal computer cost; Semiconductor tools cost; Software; Technology laws